2005
DOI: 10.1099/mic.0.27437-0
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR elements in Yersinia pestis acquire new repeats by preferential uptake of bacteriophage DNA, and provide additional tools for evolutionary studies

Abstract: The remarkable repetitive elements called CRISPRs (clustered regularly interspaced short palindromic repeats) consist of repeats interspaced with non-repetitive elements or 'spacers'. CRISPRs are present in both archaea and bacteria, in association with genes involved in DNA recombination and repair. In the Yersinia pestis genome, three such elements are found at three distinct loci, one of them being highly polymorphic. The authors have sequenced a total of 109 alleles of the three Y. pestis CRISPRs and they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
660
1
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,126 publications
(733 citation statements)
references
References 29 publications
(29 reference statements)
19
660
1
17
Order By: Relevance
“…These variable sequences, known as spacers, are juxtaposed between 2 neighboring repeats and have been shown to be highly homologous to phages or foreign genetic elements. [5][6][7][8] Thus, the CRISPR loci are described as the genetic retention of historical infections. In addition, over 45 CRISPR-associated (cas) gene families have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…These variable sequences, known as spacers, are juxtaposed between 2 neighboring repeats and have been shown to be highly homologous to phages or foreign genetic elements. [5][6][7][8] Thus, the CRISPR loci are described as the genetic retention of historical infections. In addition, over 45 CRISPR-associated (cas) gene families have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…For a small fraction of the spacers, protospacers have been reported, often in viral and plasmid genomes, but the substantial majority of the spacers remain without a match, representing vast CRISPR "dark matter" (43)(44)(45)(46)(47)(48)(49).…”
mentioning
confidence: 99%
“…However, in addition to the matches with MGEs, spacers were also found that target sites on the bacterial or archaeal genome. For example, in Yersinia spp., of 36 spacers analyzed, the majority were of bacteriophage origin, but 8 spacers matched sequences on the Yersinia chromosome (13). A similar pattern was observed in a broader analysis of 4,500 spacers across archaea and bacteria, in which 35% of the spacers that matched sequences in the NCBI database were derived from chromosomal DNA and apparently were not related to foreign elements or prophages (12).…”
mentioning
confidence: 49%
“…Analysis of the sequences of spacers from a given CRISPR array can serve as a history of previous CRISPR-Cas interactions with invading MGEs. The first evidence that CRISPRCas systems function as an immune system came from such an analysis, when in 2005, three separate groups examined a variety of CRISPR arrays and found that spacers matched sequences found in phages and plasmids (11)(12)(13). However, in addition to the matches with MGEs, spacers were also found that target sites on the bacterial or archaeal genome.…”
mentioning
confidence: 99%